THE ROLE OF ATHLETICS IN HUMAN HEALTH (Лучшие интеллектуальные исследования, 2025)
Annotation: Consistent measures are being implemented in order to popularize physical education and sports in our country, to create the necessary conditions and infrastructure for promoting a healthy lifestyle among the population, especially young people, to ensure the worthy participation of the country in international sports fields. This article provides information on the importance of movements in the flight phase in long jumpers and high jumpers. The flying phase is one of the most delicate stages for a long jumper, and at this stage it is necessary to strive to get the maximum distance by moving the body balanced, straight and controlled. Correctly selected technique gives the best result when combined with the physical capabilities of the athlete.